2016
DOI: 10.1371/journal.pone.0162986
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific MRI-Based Right Ventricle Models Using Different Zero-Load Diastole and Systole Geometries for Better Cardiac Stress and Strain Calculations and Pulmonary Valve Replacement Surgical Outcome Predictions

Abstract: BackgroundAccurate calculation of ventricular stress and strain is critical for cardiovascular investigations. Sarcomere shortening in active contraction leads to change of ventricular zero-stress configurations during the cardiac cycle. A new model using different zero-load diastole and systole geometries was introduced to provide more accurate cardiac stress/strain calculations with potential to predict post pulmonary valve replacement (PVR) surgical outcome.MethodsCardiac magnetic resonance (CMR) data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…[52] General agreement exists on the indication for PV implantation in asymptomatic patients in the presence of any of the following criteria, as judged by echocardiography and/or magnetic resonance imaging: (a) PV regurgitation >20%; (b) indexed end-diastolic right ventricular volume >120–150 ml m –2 BSA; or (c) indexed end-systolic right ventricular volume >80–90 ml m –2 BSA. [14,18,19,22,24,25] In our experience, all asymptomatic patients were matching all the accepted criteria of indication for PV implantation. The only two patients with indexed right ventricular end-diastolic volume < 150 ml m –2 BSA (respectively 130 and 142 ml m –2 BSA) were two of the four patients with associated right ventricular outflow tract obstruction.…”
Section: Discussionmentioning
confidence: 84%
“…[52] General agreement exists on the indication for PV implantation in asymptomatic patients in the presence of any of the following criteria, as judged by echocardiography and/or magnetic resonance imaging: (a) PV regurgitation >20%; (b) indexed end-diastolic right ventricular volume >120–150 ml m –2 BSA; or (c) indexed end-systolic right ventricular volume >80–90 ml m –2 BSA. [14,18,19,22,24,25] In our experience, all asymptomatic patients were matching all the accepted criteria of indication for PV implantation. The only two patients with indexed right ventricular end-diastolic volume < 150 ml m –2 BSA (respectively 130 and 142 ml m –2 BSA) were two of the four patients with associated right ventricular outflow tract obstruction.…”
Section: Discussionmentioning
confidence: 84%
“…In the construction process of both of active and passive models, the initial shrinkage rate was set as 5% to receive the zero-load geometry which is the starting geometry for the numerical simulation [33,34]. When the pressure was applied at inlet, The finite element meshes was generated by the volume component-fitting method [22,32].…”
Section: Solution Methodsmentioning
confidence: 99%
“…Two different zero-load (diastole and systole) geometries are needed to simulate ventricle diastole and systole phases, respectively. These models are called 2G models since two zero-load geometries are used [13]. The 2G model is our way to change ventricle zero-load geometry between systole and diastole phases.…”
Section: Methodsmentioning
confidence: 99%
“…Early cardiac magnetic resonance imaging (CMR)-based ventricle models were introduced by Axel and Saber et al for mechanical analysis and investigations [11, 12]. We have introduced patient-specific CMR image-based computational right and left ventricle (RV/LV) models with fluid-structure interactions (FSI) to assess outcomes of various RV reconstruction techniques with different scar tissue trimming and patch sizes [4, 5, 13, 14, 15]. A recent review can be found in [15].…”
Section: Introductionmentioning
confidence: 99%